2022
DOI: 10.3390/vaccines10071100
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa: Recent Advances in Vaccine Development

Abstract: Pseudomonas aeruginosa is an important opportunistic human pathogen. Using its arsenal of virulence factors and its intrinsic ability to adapt to new environments, P. aeruginosa causes a range of complicated acute and chronic infections in immunocompromised individuals. Of particular importance are burn wound infections, ventilator-associated pneumonia, and chronic infections in people with cystic fibrosis. Antibiotic resistance has rendered many of these infections challenging to treat and novel therapeutic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 121 publications
0
31
0
Order By: Relevance
“…Despite these considerable efforts, no vaccine has yet been found to be clinically efficacious against this pathogen. The main obstacles to achieve this goal include poor immunogenicity of the protective epitopes, a large variant subtype antigens, leading to high degree of serologic variability, a large genome facilitating adaptation to new environments, phenotypic plasticity between acute and chronic infection, and variations in animal responses to P. aeruginosa that make determination of the optimal vaccine formulations difficult from such studies [400,413]. 7.5.…”
Section: Vaccine Development Against P Aeruginosamentioning
confidence: 99%
“…Despite these considerable efforts, no vaccine has yet been found to be clinically efficacious against this pathogen. The main obstacles to achieve this goal include poor immunogenicity of the protective epitopes, a large variant subtype antigens, leading to high degree of serologic variability, a large genome facilitating adaptation to new environments, phenotypic plasticity between acute and chronic infection, and variations in animal responses to P. aeruginosa that make determination of the optimal vaccine formulations difficult from such studies [400,413]. 7.5.…”
Section: Vaccine Development Against P Aeruginosamentioning
confidence: 99%
“…Pseudomonas aeruginosa is a conditionally pathogenic bacterium widely present in nature, human skin, intestine, and respiratory tract; studies have shown that P. aeruginosa is an important causative agent of hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP) (Pang et al, 2019); notably, P. aeruginosa is prone to cause intranasal and ventilator-associated pneumonia in immunocompromised and hospitalized patients (Killough et al, 2022). Consistent with this, we found that P. aeruginosa abundance in BALF was negatively correlated with whole blood WBC counts and CD4 + T cell counts; also, in this study, we found that the number of bacterial species detected in BALF was elevated in the immunodeficient group relative to the non-immunodeficient group (Supplementary Figure 7A).…”
Section: Correlation Of Abundance Of Potentially Pathogenic Bacteria ...mentioning
confidence: 99%
“…Interestingly, although the use of LPS in vaccines can have considerable side effects, in this study, the administration of EVs without modification or removal of LPS did not seem to generate unwanted effects [ 82 ]. Most studies using well-characterized Pseudomonas antigens for vaccine development in the last 50 years have been unsuccessful [ 83 ]. Only a small number of them have entered clinical trials.…”
Section: Extracellular Vesicles As Biotechnological Toolsmentioning
confidence: 99%